Subtitling Strategies of Poâ€™s Utterances in Kung Fu Panda Movie - Hiroka Putra Adinusa; Rahmanti Asmarani (Universitas Dian Nuswantoro, 2018)
Abstract. This research is entitled â€œSubtitling Strategies of Poâ€™s Utterances in Kung Fu Panda Movieâ€. The aim of this research is to find out the subtitling strategies of Poâ€™s Utterances in Kung Fu Panda Movie. This research used descriptive qualitative method to describe then analyze the subtitling strategies of Poâ€™s utterances in Kung Fu Panda movie. The steps of analyzing data are: collecting the data, identifying the data, classifying the data, analyzing the data, and the last step is drawing the conclusion. Transfer strategy has the most frequency in Poâ€™s utterances in Kung Fu Panda movie, the percentage reaching 53,91% over half of Poâ€™s utterances. Transfer strategy is translated more easily because this strategy translating the source language completely and accurately into the target language. So it is easy to make the audience understand from the source language to the target language with the original meaning from this movie. Meanwhile, transcription has the least frequency in Poâ€™s utterances, the percentage is 2,90%. Transcription strategy is found rarely because this strategy is used to translate a language when there exist unusual term in the source language (SL), like nonsense language and third language. So it is difficult to find out transcription strategy in Kung Fu Panda movie.Keywords: Subtitling Strategies, Transcription, Transfer, UtterancesAbstrak. Â Penelitian ini berjudul â€œStrategi Penerjemahan pada Ujaran Po sebagai tokoh utama di Film â€œKung Fu Pandaâ€ dengan tujuan untuk mengetahui strategi penerjemahan ujaran Po di film Kung Fu Panda. Penelitian ini menggunakan metode deskriptif kualitatif untuk menjelaskan dan menganalisis strategi penerjemahan ujaran Po di film â€œKung Fu Pandaâ€. Tahapan-tahapan analisis adalah : mengumpulkan data, Â mengidentifikasi data, Â mengelompokkan data, menganalisis data, dan tahap terakhir adalah mengambil kesimpulan. Strategi transfer memiliki frekuensi paling tinggi dalam ujaran Po di film Kung Fu Panda, dengan persentase mencapai 53,91% lebih dari setengah ujaran Po. Strategi transfer merupakan strategi yang lebih mudah digunakan karena strategi ini menerjemahkan bahasa sumber secara lengkap dan akurat ke dalam bahasa sasaran. Jadi lebih mudah untuk membuat penonton mengerti bahasa sumber ke bahasa target melalui makna asli dari film tersebut. Sementara, transkripsi memiliki frekuensi terendah dalam ujaran Po, persentasenya 2,90%. Strategi transkripsi jarang ditemukan karena strategi ini digunakan untuk menerjemahkan bahasa ketika ada istilah yang tidak biasa dalam bahasa sumber (BS), seperti kata-kata yang tidak bermakna atau bahasa lain. Dengan demikian strategi transkripsi tidak banyak ditemukan dalam film â€œKung Fu Pandaâ€ ini.Kata kunci: strategi penerjemahan, transkripsi, transfer, ujaran